Determination of soil permeability coefficient following an updated grading entropy method. Issue 1 (21st February 2020) - O'Kelly, Brendan C; Nogal, María
Abstract : This paper presents a critical review of the grading entropy approach of permeability-coefficient predictions ( k P ) for coarse-grained soils. The approach applies the grading entropy theory to particle-size distributions (PSDs), such that the entirety of each gradation curve can be interpreted as a single point on a grading entropy chart, plotting its normalised entropy increment ( B ) against relative base grading entropy ( A ) values. Published data sets of measured permeability-coefficient ( k M ) values for saturated compacted silty sand, sand and gravel materials are examined to understand the dependence of A and B on various gradation parameters and the void ratio ( e ). In particular, log  k M negatively correlates with log  B and positively correlates with log  A and e (log  e ). As such, power functions of the form k P = C 1 A C 2 B C 3 e C 4 prove statistically superior, noting that the fitting coefficient C 1 to C 4 values are specific to the PSD range and densification (compaction) states investigated for the permeability tests. Recommendations are given for increasing the predictive power, including separate models for well-graded and poorly graded materials and the addition of a particle shape factor and specific surface parameters in the regression correlation.